Electronic cigarettes: a survey of perceived patient use and attitudes among members of the British thoracic oncology group. Issue 1 (December 2016) - Sherratt, Frances; Newson, Lisa; Field, John
Abstract Background Smoking cessation following lung cancer diagnosis has been found to improve several patient outcomes. Electronic cigarette (e-cigarette) use is now prevalent within Great Britain, however, use and practice among patients with lung cancer has not as yet been explored. The current study aims to explore e-cigarette use among patients and examine current practice among clinicians. The results have important implications for future policy and practice. Methods Members of The British Thoracic Oncology Group (BTOG) were contacted via several e-circulations (N = 2, 009), requesting them to complete an online survey. Of these, 7.7 % (N = 154) completed the survey, which explored participant demographics and smoking history, perceptions of patient e-cigarette use, practitioner knowledge regarding sources of guidance pertaining to e-cigarettes, and practitioner advice. Results Practitioners frequently observed e-cigarette use among patients with lung cancer. The majority of practitioners (81.4 %) reported responding to patient queries pertaining to e-cigarettes within the past year; however, far fewer (21.0 %) felt confident providing patients with e-cigarette advice. Practitioner confidence was found to differentiate by gender (p = 0.012) and employment speciality (p = 0.030), with nurses reporting particularly low levels of confidence in advising. The results also demonstrate extensive variability regarding the practitioner advice content. Conclusions The results demonstrate that patients refer to practitioners as a source of e-cigarette guidance, yet few practitioners feel confident advising. The absence of evidence-based guidance may have contributed towards the exhibited inconsistencies in practitioner advice. The findings highlight that training should be delivered to equip practitioners with the knowledge and confidence to advise patients effectively; this could subsequently improve smoking cessation rates and patient outcomes.